Assessment of Complete Immunization Coverage in Infants Aged 0-12 Months - Liananiar Liananiar; Yuswita Yuswita; Nuraina Nuraina; Yulia Ernida; Anna Malia; Siti Rahmah (International Journal of Health and Medicine, 2024)
Achievement of Complete Basic Immunization (IDL) in eleven Indonesian provinces in 2022 is still below the national target of 90%. The eleven provinces in question are West Sulawesi, Southeast Sulawesi, Maluku, East Nusa Tenggara, North Kalimantan, Riau, West Kalimantan, West Papua, West Sumatra, Papua and Aceh.The type of research used in this research is descriptive observational research. The data used in this study is secondary data, namely monthly reports on the results of routine immunizations for babies. It was found that the majority of basic immunization coverage for babies born in January 2022 was higher than for babies born in January 2023. Coverage for basic immunization types for babies was highest in 2022. (73.3%) was obtained from Hepatitis B, BCG, and Polio 1 immunization. The highest coverage of basic types of infant immunization in 2023 was obtained from Hepatitis B immunization (73.3%). Hepatitis B immunization received a high score for babies born in January 2022. Coverage of basic immunization types for babies born in January 2022 for types DPT-HB-Hib 1, 2, 3, Polio 2, 3, 4, received 36.7% -73, 3%, and Measles-Rubella got 33.3%. The frequency of immunization against PVC-1 (23.3%), RV-1 (6.7%), and IPV-1 (13.3%) is still low due to not visiting posyandu and giving immunizations past the immunization deadline. The average value of basic immunization coverage for babies born in January 2023 (10%) is lower than babies born in January 2022 (43.3%) with a difference of 33.3%.